KEBIJAKAN DESAIN PEMBELAJARAN DALAM OPTIMALISASI PENGGUNAAN TEKNOLOGI PADA SMP SWASTA BUDISATRYA MEDAN - Khoiriyah Syaharani Ritonga; Makmur Syukri (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the role of school learning policies in integrating digital technology into the learning process, examine the suitability between technology-based learning policy designs and digital learning practices, and formulate strategies for optimizing the use of technology to improve the quality of learning at Budisatrya Private Middle School, Medan. Methods: This research employed a qualitative approach with descriptive methods. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was tested using source and technique triangulation. Results: The research results show that school policies have supported the integration of digital technology through the provision of learning facilities and infrastructure, internet access, and the use of digital media and platforms in teaching and learning activities. However, implementation has not been optimal due to differences in teachers' digital competencies, the lack of uniform technology standards, and limited use of technology in interactive and collaborative learning activities. Supporting factors include the availability of technological facilities, school management support, and student enthusiasm, while inhibiting factors include diverse teachers' digital competencies and the potential for digital distractions.